Gender-specific reference ranges of the vocal extent measure in young and healthy adults. (2nd April 2020) - Freymann, Marie-Louise; Mathmann, Philipp; Rummich, Julius; Müller, Constanze; Neumann, Konrad; Nawka, Tadeus; Caffier, Philipp P.
Abstract: Objective: The recently developed vocal extent measure (VEM) quantifies a patient's vocal capacity as documented in the voice range profile (VRP). This study presents the first reference ranges of the VEM for young subjects without voice complaints. Furthermore, this study investigates the influence of gender on the VEM as well as the correlation of the VEM with the dysphonia severity index (DSI). Patients and methods: Reference ranges were captured by combining a retrospective analysis of subjects who received a medical fitness certificate of a healthy voice ( n = 135) and a prospective analysis of adult volunteers without voice complaints ( n = 67). Every participant obtained a standardized voice assessment comprising videolaryngostroboscopy, auditory-perceptual analysis, acoustic analysis, VRP, and the Voice Handicap Index (VHI-9i). Results: A total of 202 subjects were recruited and investigated. Due to our stringent selection criteria, 51 participants had to be excluded from further analysis. The remaining data of 151 participants (52 males, 99 females), aged 18–39 years (mean 24, SD 5), were analysed in more detail. The mean of the VEM amounted to 123.7 (SD 12.6) for males and 114.4 (SD 13.3) for females. The values differed significantly between both sexes and correlated significantly with the corresponding DSI values. Conclusion: By introducing the first reference values, this study represents the next step of implementing the VEM in daily phoniatric diagnostics. These values serve as a basis to interpret the VEM regarding the degree of severity of voice disorders and to evaluate treatment success.